2021
DOI: 10.3390/pathogens10030334
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Trypanosoma spp. in European Mammals: A Brief Journey amongst the Neglected Trypanosomes

Abstract: The genus Trypanosoma includes flagellated protozoa belonging to the family Trypanosomatidae (Euglenozoa, Kinetoplastida) that can infect humans and several animal species. The most studied species are those causing severe human pathology, such as Chagas disease in South and Central America, and the human African trypanosomiasis (HAT), or infections highly affecting animal health, such as nagana in Africa and surra with a wider geographical distribution. The presence of these Trypanosoma species in Europe has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 139 publications
0
12
0
Order By: Relevance
“…On the contrary, for Trypanosoma , the present study shows a low occurrence and a low level of parasitemia. Since trypanosomiasis is considered a tropical disease, and most of the clinical cases reported in Europe have been linked to globalization and travels, there are only a few Trypanosoma species occurring naturally in European wildlife, including T. lewisi , T. melophagium or T. theileri [ 40 ]. In this context, studies about trypanosome species identification are scarce; however, some authors have published the detection of T. corvi , T. bennetti and T. avium in wild birds from Central and Northern Europe [ 12 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, for Trypanosoma , the present study shows a low occurrence and a low level of parasitemia. Since trypanosomiasis is considered a tropical disease, and most of the clinical cases reported in Europe have been linked to globalization and travels, there are only a few Trypanosoma species occurring naturally in European wildlife, including T. lewisi , T. melophagium or T. theileri [ 40 ]. In this context, studies about trypanosome species identification are scarce; however, some authors have published the detection of T. corvi , T. bennetti and T. avium in wild birds from Central and Northern Europe [ 12 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Sulawesi is a globally significant biodiversity hotspot for terrestrial vertebrates that is also likely to support substantial undocumented parasite diversity. Research on rodents was held on two (2) 20 A study in Abu Alnomros Center, Giza, from November to March 2016 showed trypanosomiasis prevalence among the different rodent species was (21 rats) 24.7%. All the infected rats belonged to R. rattus spp., where the prevalence of infection with T. lewisi among that species was very high, 51.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Megatrypanum trypanosomes have been detected in cattle and wild bovids in Belgium, Italy, Ireland and Spain ( Doherty et al, 1993 ; Verloo et al, 2000 ; Villa et al, 2008 ; Amato et al, 2019 ; Bittner et al, 2019 ) as well as in wild cervid species, including roe deer, fallow deer and red deer in Sweden, Germany and Austria ( Friedhoff et al, 1984 ; Hoffmann et al, 1984 ; Hinaidy, 1987 ; Garcia et al, 2011 ; Neumüller et al, 2012 ); however, little data exists about their occurrence in Eurasian moose ( Kingston et al, 1985 ; Neumüller et al, 2012 ). Megatrypanum trypanosomes are generally non-pathogenic, causing only subclinical infection ( Matsumoto et al, 2011 ; Magri et al, 2021 ), which might be one of the reasons for random detection of the parasite in some cervid species.…”
Section: Discussionmentioning
confidence: 99%